1996
DOI: 10.1111/j.1525-1314.1996.00056.x
|View full text |Cite
|
Sign up to set email alerts
|

Metallogenesis of the late Pan‐African gold‐bearing East Ouzzal shear zone (Hoggar, Algeria)

Abstract: A B S TR A CT In the W Hoggar (Algeria), the major transcurrent N-S East Ouzzal shear zone (EOSZ) hosts several world-class gold deposits over a 100-km length. The late Pan-African EOSZ separates two contrasting Precambrian domains: the Archaean In Ouzzal block to the west (orthogneisses with subordinate metasediments, reworked and granulitized in the c. 2 Ga Eburnean event) and a Middle Proterozoic block to the east (again orthogneisses and metasediments, involved in the c. 600 Ma Pan-African event).The EOSZ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 28 publications
0
17
0
Order By: Relevance
“…In addition, a gold halo is developed within the alteration envelope (beresite, see below) of the quartz lodes, with contents varying from 1 ppb to 15 ppm (ORGM, unpublished data). This district is by far the best studied of all within the Hoggar province, being well described in several publications (e.g., Ferkous and Leblanc 1995;Semiani 1995;Marignac et al 1996;Ferkous and Monié 2002;and references therein).…”
Section: In Ouzzal Deposits: the Tirek-amesmessa Districtmentioning
confidence: 97%
See 4 more Smart Citations
“…In addition, a gold halo is developed within the alteration envelope (beresite, see below) of the quartz lodes, with contents varying from 1 ppb to 15 ppm (ORGM, unpublished data). This district is by far the best studied of all within the Hoggar province, being well described in several publications (e.g., Ferkous and Leblanc 1995;Semiani 1995;Marignac et al 1996;Ferkous and Monié 2002;and references therein).…”
Section: In Ouzzal Deposits: the Tirek-amesmessa Districtmentioning
confidence: 97%
“…Retrogressive metamorphism occurred concurrently with deformation and resulted in rehydration of earlier metamorphic rocks under low-grade conditions (biotite-chloriteactinolite-carbonate paragenesis). Syn-kinematic mafic bodies (mainly, gabbros) are intrusive into the mylonite, and stable isotope (O, C) studies showed that the early CO 2 -rich fluids percolating the shear-zone were of mantle derivation (Marignac et al 1996). Thus, the EOSZ is of lithospheric scale.…”
Section: The East Hoggar and Central Hoggar Metacratonsmentioning
confidence: 98%
See 3 more Smart Citations